The Impact of Social Media Promotion on Purchasing Decisions at Jetiga Ala Caffe - Syamsurizal; Ka'bah, Iffah Fuztu Warobil (International Publisher (YAPENBI), 2023)
This research aims to determine the impact of social media promotions on purchasing decisions at Jetiga Ala Cafe. This research uses quantitative methods, with non-probability sampling techniques and sampling using accidental sampling. The population in this study was 188 cafe-style Jetiga Instagram followers with a sample size of 128 respondents used in this study. Based on the data obtained, the calculated t value is 10.196 with a significance of 0.000 <0.05. It can be concluded that social media promotion has a positive and significant effect on purchasing decisions, and based on the coefficient of determination test, the R Square value is 0.452 or 45.2% of the purchasing decision variable. influenced by social media promotions while the rest is influenced by other factors not discussed in this research.